THE SUSTAINABLE MANAGEMENT OF POST-MINING LANDUSE; AN AHP APPROACH A CASE STUDY: EX-SAND MINING IN INDRAMAYU REGENCY, WEST JAVA - Hamdani, Ahmad Helman; Hutabarat, Johanes; Muhamadsyah, Faisal (Journal of Geological Sciences and Applied Geology, 2021)
Recently, the sustainable management of post-mining land use has received great attention. The mining-closure, due to the mine has no longer economic value, or the mined material has run out; often leaving poor landscapes and degraded land.  The mining company have to rehabilitate the ex-mining land so that it can be returned to its original baseline stage or can be used for other more useful activities. The objective of research is to arrange the sustainable management plan of post-mining land use at ex sand-mining in Indramayu Regency, West Java. The Analytical Hierarchy Process (AHP) approach used to determine the priority of activities that will be carried out on the land. Several criteria and alternative were calculated by Saaty’s AHP pairwise comparison scale.  The research results reveal that in post mining land use management based on sustainable management, economic criteria must be considered first, followed by environmental, socio-culture and finally technical criteria. Fishery, cattle breeding and agriculture were found to be the optimal alternative for sand post‐mining land use.